PEMAHAMAN SISWA SMA TENTANG ARTI MARKA JALAN DAN PERATURAN LALU LINTAS - Achmad Hercahyo Jatiputro; Ika Setiyaningsih; Gotot Slamet Mulyono (Universitas Muhammadiyah Surakarta, 2015)
The rapid development of Surakarta closely impact on people mobility and transportation in the city. It can be seen from traffic volume increasing on some major roads in Surakarta. At peak hour, traffic in Surakarta is dominated by motorcycle. According to Police Traffic Unit of Surakarta data, the highest ranked accident by the type of mode of transportation is a mo-torcycle and the highest accident victims in the productive age which is 16-30 years. By education level, the highest number of traffic violations conducted by the level of high school education. Based on this condition it is necessary to do research on the characteristics of high school students who use motorcycles. The focus of this research is to determine high school student understanding of the road markings meaning and traffic regulations. This study uses a questionnaire tools that have previously been tested for validity and reliability. Research sample is high school student of Batik 2 Surakarta with a total sample of 140 respondents.The results showed that the level understanding to road markings obtained 78 respondents are very understand, 51 respondents including category of understand and as many as 11 respondents do not understand. The results showed that the level understanding to road markings obtained 78 respondents are very understand, 51 respondents including category of understand and as many as 11 respondents do not understand. While the results of the discussion on the understanding of traffic regulations showed the respondents' level of understanding with the three classifications which is very understand there were 121 respondents, 19 respondents are understand classification and classification do not understand as much as 0 respondents.